DNA-Binding and Topoisomerase-I-Suppressing Activities of Novel Vanadium Compound Van-7 - Xiao-mei Mo; Zhan-fang Chen; Xin Qi; Yan-tuan Li; Jing Li (Bioinorganic Chemistry and Applications)
Vanadium compounds were studied during recent years to be considered as a representative of a new class of nonplatinum metal anticancer agents in combination to its low toxicity. Here, we found a vanadium compound Van-7 as an inhibitor of Topo I other than Topo II using topoisomerase-mediated supercoiled DNA relaxation assay. Agarose gel electrophoresis and comet assay showed that Van-7 treatment did not produce cleavable complexes like HCPT, thereby suggesting that Topo I inhibition occurred upstream of the relegation step. Further studies revealed that Van-7 inhibited Topo I DNA binding involved in its intercalating DNA. Van-7 did not affect the catalytic activity of DNase I even up to100 μM. Van-7 significantly suppressed the growth of cancer cell lines with IC50 at nanomolar concentrations and arrested cell cycle of A549 cells at G2/M phase. All these results indicate that Van-7 is a potential selective Topo I inhibitor with anticancer activities as a kind of Topo I suppressor, not Topo I poison.